A Population-Based Analysis of Interpersonal Trauma, Psychosis, and Suicide: Evidence, Pathways, and Implications - Boyda, David (Journal of interpersonal violence, 2022)
Subthreshold psychotic experiences (PEs) are known to confer a risk for suicidality. Yet, despite evidence of a strong etiological trauma–psychosis pathway, the coalesced effect of such concurrences on suicide risk is largely discounted. Our aims were to examine the impact of different manifestations of life span trauma and PEs on the risk of suicidal thoughts and attempts, using an exploratory person-centered approach. Data from the Adult Psychiatric Morbidity Survey (N = 7,403) were analyzed. PEs were assessed using the Psychosis Screening Questionnaire (PSQ) alongside items probing childhood and adult trauma, in addition to 12-month suicide thoughts and attempt. A manual three-step latent class analysis elicited four distinct profiles, namely, a socially disconnected/high PE, a sexual victimization/moderate PE, a life span trauma/low PE, and a baseline class. The socially disconnected class, characterized by a moderate likelihood of social disconnection, a high probability of various PE endorsements, yet a low likelihood of other significant trauma, showed the greatest risk of 12-month suicide ideation (odds ratio [OR] = 13.0, 95% confidence interval [CI] = [8.539, 19.021) and attempt (OR = 24.2, 95% CI = [10.349, 56.860). Neither multiple nor recurrent traumatic experiences invariably result in the emergence of PEs. Instead, a sense of social disconnection may be either resultant of PEs or alone sufficient to cultivate such symptom presentations, even in the absence of prior traumas. Moreover, just as traumatic encounters increase the risk of suicidality, so too might seemingly more innocuous adversities, such as poor-quality social relationships, further elevate the risk, particularly when proximal and coupled with the simultaneity of PEs.